(untitled) (The International Journal for Scientific Research, 2025)
3D printing is revolutionizing the cultural and artistic landscapes, notably impacting live arts and scenography by enabling the crafting of complex and tailored designs with unparalleled efficiency. This technology, pivotal to the fourth industrial revolution, transforms imaginative concepts into tangible reality, fostering new pathways for creative exploration. This article investigates 3D printing’s profound influence on the theatrical domain, particularly in scenography. It facilitates the creation of groundbreaking decorations and costumes, thus elevating the performance experience and deepening audience engagement. Through a survey conducted among artists in the Arab cultural sector, the study evaluates the contributions of 3D printing to live arts. The findings spotlight the technology’s effectiveness in enhancing scenographic elements and underscore the vital role of artificial intelligence in generating unique scenographic designs. Positioning 3D printing as a significant innovation in scenography and a catalyst for creativity in live arts, the article anticipates a future where advanced technology is seamlessly woven into artistic practices. The insights gleaned from the survey and hands-on experiments underscore 3D printing’s potential to foster novel artistic expressions, indicating a movement towards an innovative and efficient integration of technology within live arts.